DAMPAK POSITIF DAN NEGATIF DALAM PENERAPAN INTERNASIONAL FINANCIAL REPORTING STANDARS (IFRS) DI INDONESIA - Evi Maulida Yanti; Zulfikar Zulfikar; Muliana Muliana; Achma Mutacha (Jurnal Real Riset, 2020)
The objective of the establishment of the International Accounting Standards Committee (IASC) and the International Accounting Standards Board (IASB) is to develop high quality international financial reporting standards. This is in line with the mandate of the G-20 meeting in London to have a set of high-quality global accounting standards in order to provide quality financial information on international capital markets. To achieve this goal, the IASC and IASB have issued principles-based standards called International Financial Reporting Standards (IFRS) and previously International Accounting Standards (IAS). IFRS has been implemented in Indonesia since 2012. In practice, the government requires several institutions to use this IFRS system. Institutions that are required to use the IFRS system according to government regulations are banking, insurance, public companies, and BUMN. The research uses a descriptive method with the aim of gathering information about IFRS. The conclusions that can be drawn are the positive things from the application of IFRS in Indonesia, namely opening opportunities for entrepreneurs to spread their wings in the international world and the negative impact that occurs is that entrepreneurs who are less creative in developing their business will be increasingly left behind because foreign entrepreneurs are starting to enter Indonesia.Keywords : IASC, IASB, IFRS, Financial Reporting Standards